SAVI (SOMATIS, AUDITORI, VISUAL DAN INTELEKTUAL) SEBAGAI ALTERNATIF PEMBANGKIT KECERDASAN TERPADU SISWA DI ERA SOCIETY 5.0 - Nur Wahidah; Asnawan; Ifa Afida (International Conference on Humanity Education and Society (ICHES), 2024)
In the current era of Society 5.0, education actors are required to be able to integratesophisticated technology into the life of their school environment in a smarter way.This makes educators more agile in innovating in the learning activities they carryout, especially in choosing learning approaches, through the use of technologicalmodernity in the digital era like this. SAVI (Somatic, Auditory, Visual and Intellectual)is a compatible approach when applied in learning activities in the current SuperSmart era. The research conducted is not the first research, but there have been several related studies. This research method uses the Theoretical Research method,presenting information through relevant sources using topics and not usingempirical methods. Using the SAVI learning approach can raise students' enthusiasmfor learning, especially in developing students' integrated intelligence. SAVI is analternative source of fully integrated intelligence for students, with the help ofsophisticated technology in the Society 5.0 era. Furthermore, by using the SAVIapproach which involves the connection of the body and the five senses along withintellectual activities, the learning carried out will have an effective, efficient impactand classroom management will definitely be better